Assessing the role of lipid-lowering therapy on multi-cancer prevention: A mendelian randomization study - Min, Yu; Wei, Xiaoyuan; Liu, Zheran; Wei, Zhigong; Pei, Yiyan; Li, Ruidan; Jin, Jing; Su, Yongllin; Hu, Xiaolin; Peng, Xingchen (Frontiers in Pharmacology, 2023)
Background Statin use for cancer prevention has raised wide attention but the conclusions are still controversial. Whether statins use have exact causal effects on cancer prevention remains unclear. Methods Based on the Genome-Wide Association Studies (GWAS) datasets from the large prospective UK Biobank and other consortium databases, two-sample mendelian randomization (MR) analysis was conducted to explore the causal effects of statins use on varied site-specific cancer risks. Five MR methods were applied to investigate the causality. The stability, heterogeneity, and pleiotropy of MR results were also evaluated. Results The atorvastatin use could increase the risk of colorectal cancer (odd ratio (OR)=1.041, p=0.035 by fixed-effects inverse variance weighted (IVW) method (IVWFE), OR=1.086, p=0.005 by weighted median; OR=1.101, p=0.048 by weighted mode, respectively). According to the weighted median and weighted mode, atorvastatin could modestly decrease the risk of liver cell cancer (OR=0.989, p=0.049, and OR=0.984, p=0.004, respectively) and head and neck cancer (OR=0.972, p=0.020). Besides, rosuvastatin use could reduce the bile duct cancer risk by 5.2% via IVWEF method (OR=0.948, p=0.031). No significant causality was determined in simvastatin use and pan-cancers via the IVWFE or multiplicative random-effects IVW (IVWMRE) method if applicable (p>0.05). There was no horizontal pleiotropy observed in the MR analysis and the leave-one-out analysis proved the stability of the results. Conclusions The causalities between statin use and cancer risk were only observed in colorectal cancer and bile duct cancer in the European ancestry population. Future works are warranted to provide more robust evidence for supporting statin repurposing for cancer prevention.